Control Interno de la Ferretería “El Maestro” del Cantón (Jujan) - Maridueña Cardenas, Ruth Betzabeth (2018)
The present case study will deal with the importance of internal control within of the hardware store "El Maestro" of the canton Alfredo Baquerizo Moreno (Jujan). The Hardware "El Maestro", currently performs all its activities in accordance with the practice in which he has worked the other years, however, problems continue to be evident, because there are deficiencies in compliance with internal control, which is why it leads us to identify what are the causes and situations for the hardware store does not meet its goals. The Internal Control is a series of control actions that happen constantly, from according to the functioning of each entity, and must be present in the structure administratively, for the achievement of its objectives. It should be noted that the sub line of research with which the present case study is available is management of accounting information. The methods were used: the observation method and the descriptive method, as a technique of investigation the interview was used and as a research tool the questionnaire. The purpose of this case study is based on the identification of the various causes and situations that affect the moment of fulfilling the internal control and therefore has as result not being able to reach the proposed goals.